Stesikhoros and Helen - Kelly, A (Schweizerischen Vereinigung für Altertumswissenschaft, 2007)
The famous story of Stesikhoros’ encounter with Helen can be explained as a biographical derivation from the structure itself of a single ‘hymnodic’ poem composed in honour of that figure. Known in antiquity as either the Helen or the Palinode, this poem employed a persona narrative (probably) in its first section, and it did so principally in order to establish Stesikhoros’ authority against the background of Homeric and Hesiodic treatments. This episode then gave rise to stories both about the author (his blindness) and his text (two compositions, and then even two Palinodes). After considering the evidence for such encounters in Archaic and Classical Greek poetry and how they might be reconciled with the fragments and testimonia, the article discusses the problems with those sources which multiply the Helen / Palinode, and closes with a brief reconstruction of the poem according to the current hypothesis.